2016
DOI: 10.1111/clr.12846
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐β, interleukin‐17, and IL‐23 gene expression profiles associated with human peri‐implantitis

Abstract: Data presented in this report demonstrated a predominant Th17 response in peri-implantitis subjects based on the higher levels of IL-23 and lower levels of TGF-β detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…If Th17 signaling is activated, then differentiation into Treg and Th2 cells is suppressed, and TGF‐β is decreased . In a study by Gustavo Pereira Mardegan and colleagues, a predominant Th17 response was demonstrated in subject with peri‐implantitis, and a lower level of TGF‐β was also observed . Therefore, the tendency of TGF‐β is a result of the CyPA concentration and Th17 cell activation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If Th17 signaling is activated, then differentiation into Treg and Th2 cells is suppressed, and TGF‐β is decreased . In a study by Gustavo Pereira Mardegan and colleagues, a predominant Th17 response was demonstrated in subject with peri‐implantitis, and a lower level of TGF‐β was also observed . Therefore, the tendency of TGF‐β is a result of the CyPA concentration and Th17 cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Th17 cells emerge parallel to Th1 cells, and they may interact in the inflammatory process . If Th17 signaling is activated, then differentiation into Treg and Th2 cells is suppressed, and TGF‐β is decreased . In a study by Gustavo Pereira Mardegan and colleagues, a predominant Th17 response was demonstrated in subject with peri‐implantitis, and a lower level of TGF‐β was also observed .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…45 Interestingly, a recent study investigating the IL-17, IL-23, and TGF-β gene expression levels in healthy and diseased peri-implant tissues showed a predominant Th17 response and a diminution of Treg response in the presence of peri-implantitis when compared to peri-implant healthy condition, especially caused by the up-regulation of IL-23 and down-regulation of TGF-β observed in peri-implantitis tissues. 46 Importantly, a systematic review of Duarte et al, 47 aimed to define if cytokine levels in the fluid around implants could be employed to differentiate healthy implants and those with peri-implantitis, pointed-out that most of studies include in the review described statistically significantly augmented concentration of pro-inflammatory mediators in the peri-implant fluid of dental implants with peri-implantitis than in the peri-implant crevicular fluid of healthy implants, whereas many investigations did not find any significant differences in the peri-implant crevicular fluid levels of anti-inflammatory cytokines.…”
Section: Pro-and Anti-inflammatory Mediatorsmentioning
confidence: 99%